Impressão termográfica na detecção de claudicação em cães - Garcia, Érika Fernanda Villamayor (2013)
Thermography is a non-invasive imaging diagnostic technique that records thermal patterns generated by infrared emission of heat from the body surface based on the local cutaneous perfusion. These thermal patterns are converted and displayed on a color map. In horses, since the 60s have been used for the detection of various orthopedic injuries and, in recent years studies in dogs have been published. Locomotion is the process by which the animal moves from one geographic location to another. The study of locomotion is essential to establish methods for treating disorders of the locomotor apparatus. Examination of the gait is the first step for the diagnostic in the evaluation of a patient with claudication. The aim of this study was to establish the thermal patterns of the paw prints of dogs with lameness compared to healthy dogs. It was verified also if there are differences in the temperature of paw print of the lame limb versus normal limb of normal dog and weight bearing limb of lame dog versus normal limb of normal dog. It was used 14 dogs with unilateral pelvic limb lameness due to rupture of the cranial cruciate ligament (lame limb versus weight bearing limb) and 14 healthy dogs (right limb versus left limb). Thermographic images of the paw print were made after the dog remained in an orthostatic position on foam mat for 30 seconds. It was analyzed average temperatures and thermal patterns. Gait analysis was performed on a force platform in the same position to measure the peak vertical force (PVF). It was calculated mean, standard deviation, percentage of average, and asymmetry index for this variable of the gait. There were no significant differences in the temperature of the paw print between groups. Analysis of the pattern of thermal images showed 80% success in differentiating lame limb versus weight bearing limb (abnormal group) and 100 % in the identification of the same thermal pattern between right limb compared to the left limb (normal group). The mean of the PVF showed 10.0 % difference in normal dogs and 72.4 % in abnormal dogs. Analysis of asymmetry index showed 5 % in the normal group and 36.2 % in the abnormal group. It is conclude that the thermal paw print can be successfully used as an additional tool for the detection of the pelvic limb lameness in dogs.